The Capital Structure Puzzle Revisited - Berens, James L.; Cuny, Charles J. (Review of Financial Studies, 1995)
Corporate finance researchers have long been puzzled by low corporate debt ratios given debt's corporate tax advantage. This article recognizes that firm value typically reflects a growing stream of earnings, while current debt reflects a nongrowing stream of interest payments. Debt to value is therefore a distorted measure of corporate tax shielding. Even with very small debt-related costs, this may explain the observed magnitude and cross-sectional variation of debt ratios. Since this variation may be independent of tax shielding, debt ratios provide an inappropriate framework for empirically examining the trade-off theory of capital structure.